EPIDEMIOLOGICAL PROFILE OF THE POPULATION WHO UNDERWENT MYOCARDIAL REVASCULARIZATION AND ACCESS TO THE UNIFIED HEALTH SYSTEM - Cintia Koerich; Gabriela Marcellino de Melo Lanzoni; Betina Hörner Schlindwein Meirelles; Maria Aparecida Baggio; Giovana Dorneles Callegaro Higashi; Alacoque Lorenzini Erdmann (Universidade Federal do Paraná, 2017)
The present study aimed to describe the epidemiological profile of a population who underwent myocardial revascularization surgery and gain insight on how this population accesses the health services for promotion, prevention, treatment and rehabilitation. Descriptive cross-sectional study with a sample of 99 participants conducted between March 2013 and February 2014. Concerning the profile of the participants, 70 (70.7%) were men, 61 (61.6%) were married, 53 (53.5.9%) were retired, 86 (86.9%) lived in the Metropolitan region and had an average age of 61.3 (± 8.5) and a mean schooling of six years (± 3.4). The prevalent comorbidities were Systemic Arterial Hypertension, 84 (84.8%) and Diabetes Mellitus, 42 (42.4%). Regarding access to health services, 49 (49.4%) were admitted to a hospital and 31 (31.3%) were assisted at a Basic Health Unit (BHU). Strategic actions aimed to facilitate access of this population to health services and their monitoring, especially in Primary Health Care (PHC), before and after myocardial revascularization surgery, is needed.